Quantitative evaluation of surface cleanliness of weathering steel treated by continuous wave laser. (February 2023) - Wang, Qidi; Kainuma, Shigenobu; Huo, Peng; Morikawa, Ryoga
Highlights: Use a high power continuous wave laser to clean corroded steel components. Proposed a quantitative evaluation method of surface cleanliness based on color difference analysis of CIE LAB color space. Laser-cleaned corroded surfaces can achieve more than 80 % cleanliness and prolong re-corrosion times for more than 2 weeks. Presented an engineering procedure for continuous wave laser cleaning on corroded steel components. Abstract: A 3 kW continuous-wave (CW) laser was used for the laser cleaning of weathering steel with artificial corrosion pits. Specimens with different degrees of corrosion were obtained by NaCl deposition in artificial pits of 10 mg/m 2, 100 mg/m 2 and 1000 mg/m 2 through constant dew point dry and wet cycles for one year. To develop quantitative evaluation methods that can be applied on-site, the cleanliness of the laser-cleaned surface was evaluated through visual observation, turning time, and photographic analysis. The results reveal that the photometric analysis based on the CIE L*a*b* color space can be used to evaluate the surface cleanliness of surfaces treated with a CW laser, which is consistent with the results of the turning time test. The color difference of the surface before and after the laser treatment can be used as a quantitative index to evaluate cleanliness. The proposed laser surface treatment procedures can provide a reference for cleaning corroded weathering steel structures and achieve cleanliness of more than 80 % and a longer turning time.